Kajian Penyebab Kemiskinan Masyarakat Nelayan di Kampung Tambak Lorok (Fishermen Poverty Causes in Tambak Lorok Village) - Mussadun, Mussadun; Nurpratiwi, Putri (The ITB Journal Publisher, 2016)
Abstract. Poverty is caused by natural, cultural as well as structural factors. In coastal areas, the conditions of poverty can be aggravated by climate change phenomena such as coastal inundation and flooding. The village of Tambak Lorok is home for more than 500 poor fishermen households. Three phenomena are considered general problems in Tambak Lorok, i.e. poverty, social pathology, and environmental degradation. In view of these problems, the following research question was formulated: âWhy and how does poverty exist among the fishermen households of Tambak Lorok?â The results of this study revealed that the natural causes of poverty among fishermen in Tambak Lorok are seasonal factors and coastal damage. Structural causes of poverty are limited access to banking capital and the fishermenâs inability to set the price for their catch. Furthermore, cultural factors are the fishermenâs consumptive behavior, debt-forming habits, and difficulty saving money. The poverty condition of the fishermen in Tambak Lorok is also worsened by the aftermath of coastal inundation and flooding. Recommendations for the government to alleviate the poverty problem of the fishermen in Tambak Lorok based on this research are to implement programs related to coastal resource rehabilitation, easing the fishermenâs access to capital, lifestyle readjustment as well as coastal inundation and flood prevention. Meanwhile, it is also recommended for the fishermen to take part in coastal resource conservation, optimizing the role of their community, and lifestyle readjustment.Â Keywords. Natural poverty, structural poverty, cultural poverty, climate change, fishermen.